2014
DOI: 10.17722/ijme.v2i3.73
|View full text |Cite
|
Sign up to set email alerts
|

Working Capital Management and Profitability Relationship-Evidences from Emerging Markets of UAE

Abstract: Abstract-

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
14
0
6

Year Published

2017
2017
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(21 citation statements)
references
References 8 publications
1
14
0
6
Order By: Relevance
“…For example, Mehta (2014) investigated the relationship of working capital management and the profitability in the real estate and construction sectors of the United Arab Emirates (UAE). The results showed a significant negative relationship between profitability and the length of the firm's cash conversion cycle.…”
Section: Factors Affecting Profitability Of Real Estate Firms Globallymentioning
confidence: 99%
See 1 more Smart Citation
“…For example, Mehta (2014) investigated the relationship of working capital management and the profitability in the real estate and construction sectors of the United Arab Emirates (UAE). The results showed a significant negative relationship between profitability and the length of the firm's cash conversion cycle.…”
Section: Factors Affecting Profitability Of Real Estate Firms Globallymentioning
confidence: 99%
“…CCC measures the number of days accounts receivable, the number of days inventories, and the number of days accounts payable, and the study of Deloof (2003) has proven that CCC influences the profitability of a company. In terms of real estate and construction industries, Mehta (2014) examined publicly-listed companies in the Abu Dhabi stock exchange and showed that with longer CCC, the lesser the profitability of the companies. Moreover, Hammes and Chen (2005) earlier noticed that the determinants of firm's profitability in one country compare to the others could be the same, but the result in the different aspects like liquidity and leverage depend on the general economic conditions of a country.…”
Section: Introductionmentioning
confidence: 99%
“…It is worth nothing that prior conclusions support the conjecture that involved in the second hypothesis which based on the existence of significant differences among Egyptian industries concerning the notion of the length of cash conversion cycle and its components. Additionally, the results indicate that there is a significant difference among scanned industries regarding the firm size as the value of significance in one way ANOVA analysis is .000 Makori, 2013;Mehta, 2014;Bagh et al,2016, Lyngstadaas andBerg,2016).…”
Section: Results Of the Relation Between CCC And Firm Sizementioning
confidence: 88%
“…While authors such as (Bhat, 1980) and (Pandey, 1985) (Liow, 2010) have examined other variables such as size of firm, growth and volatility of earnings. A league of authors (Lazaridis & Tryfonidis, 2006), (Vishnani & Shah, 2007), (Imeokparia, 2013), (Mehta, 2014) and (Mensah, 2014) has investigated the relationship of working capital and profitability. However, capital structure with long run time perspective and working capital with short run time perspective needs to be simultaneously examined with reference to their relationship with profitability and the extent of impact they have on the profitability of the enterprise.…”
Section: Need For the Studymentioning
confidence: 99%
“…(Imeokparia, 2013) also in his study of food and beverages companies of Nigeria observed a significant relationship inventory and performance of the company. (Mehta, 2014) in his research observed a significant negative association between length of cash cycle and profitability. (Mensah, 2014) in his study of manufacturing firms listed on Ghana Stock Exchange observed that debtors had significant negative association with profitability whereas the inventory had positive association with profitability of the enterprise.…”
mentioning
confidence: 93%